Menjaga Iman Kepada Hari Akhir di Era Modern: Dalam Ilmu Eskatologi - Satrio Syahbana; Fajrul Hakim; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The science of eschatology is a branch of theology concerned with the last days. In Islamic teachings, the science of eschatology is closely related to Muslims' belief in the Last Day. And for Muslims, faith must be consistent with evidence in the form of daily practice and reflect the science of eschatology or belief in the end times. The practice of science is very important because it brings many benefits and important developments to human life. In fact, there are many ways to practice or interpret the science of the end times and eschatology, one of which is to live soberly. So how can minimalist living be an eschatological practice that considers the last days and the afterlife? This article discusses the issue using qualitative research methods in the form of a literature review and literature survey. The results of this study show that minimalist living can be used as an application of the science of eschatology to remember the afterlife. Minimalist living is fundamentally similar to the life of the Qanaah and the Zhud, both of which focus on the afterlife and death. In addition, Islamic teachings have long advocated minimalist living, which is a simple life and not excessive in order to realise the world and multiply practices to improve the quality of life after death.